2018
DOI: 10.1071/hc18018
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ perceptions of team-based care in family practice: access, benefits and team roles

Abstract: INTRODUCTION:The increasing complexity of health care and escalating prevalence of multiple chronic conditions have driven interprofessional team-based care in family practice. Most published studies examine team-based care from the perspective of health professionals. The purpose of this study was to examine patients' perceptions of team-based care in family practice. METHODS:This was a waiting room survey conducted in five family medicine academic teaching clinics in Edmonton, Alberta, Canada. Patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…From our review, there is considerable evidence that TBPCC can enhance patient experience of care through strategies related to accessibility, respectful supportive relationships, enhanced opportunities for knowledge sharing, self-management, and community advocacy (24,33,34,40). The availability of enhanced case management or specialized support roles also positively influences patient experience (44,45,72).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…From our review, there is considerable evidence that TBPCC can enhance patient experience of care through strategies related to accessibility, respectful supportive relationships, enhanced opportunities for knowledge sharing, self-management, and community advocacy (24,33,34,40). The availability of enhanced case management or specialized support roles also positively influences patient experience (44,45,72).…”
Section: Discussionmentioning
confidence: 95%
“…Four of the seven studies from the Prairie Provinces (Alberta=6, Manitoba=1) mapped to the Quadruple Aim. Two studies reported on patient experience (33,34), one on population health (35), and one on provider experience (36). Three of seven studies reported on team collaboration and function as important components of transitioning to TBC (36)(37)(38).…”
Section: Prairie Provincesmentioning
confidence: 99%
See 2 more Smart Citations
“…Szafran's team from Canada show how patients value the team-based care that has been implemented in Canadian primary care clinics for more than a decade 17 and McKinlay's team extend our knowledge about the importance of social networks by testing the knowledge in general practice about patients' social networks by the statements of patients themselves of their own networks. 18 Strobel et al use routinely collected data to examine process of care indicators for indigenous children in Australia.…”
Section: Reading Writing and Research Impactmentioning
confidence: 99%